Measuring helium bubble diameter distributions in tungsten with grazing incidence small angle x-ray scattering (GISAXS). (11th January 2016) - Thompson, M; Kluth, P; Doerner, R P; Kirby, N; Riley, D; Corr, C S
Abstract: Grazing incidence small angle x-ray scattering was performed on tungsten samples exposed to helium plasma in the MAGPIE and Pisces-A linear plasma devices to measure the size distributions of resulting helium nano-bubbles. Nano-bubbles were fitted assuming spheroidal particles and an exponential diameter distribution. These particles had mean diameters between 0.36 and 0.62 nm. Pisces-A exposed samples showed more complex patterns, which may suggest the formation of faceted nano-bubbles or nano-scale surface structures.